Ways to improve the cost management principles at economic entities (Eurasian Research Bulletin, 2023)
This article focuses on the development of the up-to-date proposals and recommendations on the organization of the methods of the cost management and determination of the production prime-cost in reliance upon the peculiarities of the economic entities under conditions of the economy modernization.